Pengaruh Terapi Dzikir terhadap Penurunan Gejala Halusinasi (Pendengaran) di RSJD Surakarta - Dewi, Nadila Shinta; Musta’in, Musta’in; Palupi, Dwi Lestari Mukti (Universitas Muhammadiyah Klaten, 2025)
Auditory hallucinations are one of the main symptoms experienced by patients with schizophrenia, characterized by the perception of voices such as insults, commands, or threats without any external stimulus. This condition can disrupt social functioning, increase anxiety, and impair patients’ ability to control their behavior. Pharmacological therapy remains the primary treatment; however, its side effects and patients’ low adherence highlight the need for complementary non-pharmacological interventions. This study aimed to analyze the effect of psychoreligious dhikr therapy on reducing signs and symptoms of auditory hallucinations among psychiatric inpatients at Surakarta Mental Hospital. This research employed a quasi-experimental design with a pretest–posttest control group involving 36 respondents, divided into an intervention group (n=18) and a control group (n=18). The Auditory Hallucinations Rating Scale (AHRS) was used as the measurement instrument. Dhikr therapy was administered for six consecutive days, while the control group received the hallucination-commanding technique. Data were analyzed using the Wilcoxon and Mann–Whitney tests with a significance level of 0.05. The findings showed a significant reduction in hallucination scores within the intervention group (p = 0.000), marked by a decrease in severe hallucination cases from 55.6% to 0%. In contrast, the control group demonstrated a more limited reduction, with severe symptoms remaining in 27.8% of respondents. Posttest comparison also indicated a significant difference between groups (p = 0.000). In conclusion, psychoreligious dhikr therapy is effective in reducing the intensity of auditory hallucinations and can be recommended as a non-pharmacological nursing intervention in mental health care.